Recovering of the Monterrey Metropolitan Area, Mexico, After Hurricane Alex (2010): The Role of the Nuevo Leon State Reconstruction Council - Aguilar-Barajas, Ismael; Ramirez, Aldo I. (Frontiers in Environmental Science, 2019)
The Monterrey Metropolitan Area (MMA), strategically located in Northeastern Mexico, has a population of over 4.5 million people. The metropolis is the second largest economic center in the country, only after Mexico City, and maintains a key role in the Mexico-US trade corridor. Thus, the issue of urban resilience to extreme weather events is a matter of national security and not only a local concern. In July 2010, Hurricane Alex hit the Monterrey Metropolitan Area (MMA). It is estimated that 15 human lives were lost. The hurricane generated severe damages to the metropolis’s infrastructure and economy. In the aftermath of Hurricane Alex, the Nuevo Leon State Reconstruction Council (CERNL, in Spanish) was established, with the participation of government agencies and actors from the local community (universities, non-governmental organizations, and large firms. This paper analyses the role played by the CERNL in the reconstruction of the MMA. In 2013, the CERNL ended its mission. Most basic services and infrastructure were re-established, some of them within a few days and weeks after Alex hit the MMA. The relative good work of the Council, in spite of a fragmented and dysfunctional institutional framework, has to do with a local enabling environment that facilitated its establishment and the carrying out of activities. However, this case study also shows the difficulties associated with the design and implementation of coherent, sound strategies in this governance framework. Furthermore, the metropolis has been losing the policy capabilities built through the Council. This is a very risky current context that could have serious social, economic and environmental damages to Monterrey. The lessons presented in this contribution may be of interest to other cities in Mexico and elsewhere.